A influência do controle social para a governança eletrônica: um estudo nos consórcios intermunicipais de saúde do estado do Paraná - Fabriz, Sergio Moacir (2017)
Brazil, in an attempt to broaden the coverage of the Unified Health System (SUS) in medical specialties, has decentralized the care through Intermunicipal Consortiums of Health, which face several challenges, such as high demand, few public resources, lack of transparency, and citizens’ participation. To enhance popular participation in the overseeing of public budget, the government has created and implemented both the Transparency Law and the Information Law, which demand the publicizing of Financial and Administrative Acts through the Internet. The present research had as main goal to verify the participation and the influence of social control on the electronic governance on the Intermunicipal Consortiums of Health in the state of Paraná, Brazil, starting from the question: what is the influence of social control on the electronic governance of the intermunicipal consortiums of health in the state of Paraná, Brazil? To answer such question, the level of electronic governance in the Consortiums was assessed using the Electronic Governance Index for Intermunicipal Consortiums (Índice de Governança Eletrônica dos Consórcios Intermunicipais – ICECI), and the perception of Municipal Health Councils regarding the form and the level of information made available on these institutions’ webpages. Regarding the methodology, this study has been divided in four steps: firstly, bibliographical data was assessed on electronic governance, information and communication technology, transparency, financial disclosure, Intermunicipal Consortiums of Health and social control; secondly, the identification of the Electronic Governance Index was carried out, using the Consortiums’ webpages; thirdly, the influence of Municipal Health Councils was verified in the variation of electronic governance practices implemented by the Intermunicipal Consortiums. It was found, through this study, after the application of the IGECI that the consortiums CISAMUSEP, CISMEPAR, CISCOPAR, CISCENOP, and CISI achieved the highest scores, and social control was considered a democratic and participative body, which needs capacitation programs for its counselors. The results of the regression demonstrated that the participation of the counselor and the overseeing of the counselors influence on the electronic governance indexes of the Intermunicipal Consortiums of Health. It was understood that the Consortiums can evolve their practices of electronic governance through the influence of Municipal Health Counsels